2019
DOI: 10.1088/2051-672x/ab0320
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on corrosion-fouling relationship of Ni-W-P composite coating surface of heat exchanger

Abstract: The ternary Ni-W-P coating was prepared on mild steel (1015) and the corrosion-fouling relationship was investigated. Meantime, the Ni-W-P coatings were characterized in terms of their properties and surface morphology by means of scanning electron microscope (SEM), x-ray diffraction (XRD) and electrochemical station. The result of fouling experiment shows that the Ni-W-P coating has better anti-fouling property than the uncoated mild steel surface. Additionally, both of the samples with or without Ni-W-P coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Therefore, there are not only calcium carbonate fouling but also iron rust formed on the substrate surface. The result conforms to our previous studies [10,13] and proves that Ni-W-P has an admirable effect on anti-fouling performance. After calculating the mass change of the fouled specimens, it was found that there is no obvious rule between the mass change and the W content in the coating, while the certainty is that the mass gain of fouling on all the coated specimen is less than that of the bare substrate surface in the same period.…”
Section: Surface Morphology and Microstructuresupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, there are not only calcium carbonate fouling but also iron rust formed on the substrate surface. The result conforms to our previous studies [10,13] and proves that Ni-W-P has an admirable effect on anti-fouling performance. After calculating the mass change of the fouled specimens, it was found that there is no obvious rule between the mass change and the W content in the coating, while the certainty is that the mass gain of fouling on all the coated specimen is less than that of the bare substrate surface in the same period.…”
Section: Surface Morphology and Microstructuresupporting
confidence: 93%
“…It can be seen from Figure 1 that the fouling of calcium carbonate Since the 1980s, electroless plating has been treated as an operational technology of the surface modification, attracting widespread attention [4][5][6][7][8]. The results prove that electroless Ni-P-based coating is an advantageous method for fouling inhibition [9][10][11][12][13]. The mass gain method [10,11,14], the calcium ion loss method [12], and the fouling resistance method [15] were commonly used for measuring the deposition process of calcium carbonate fouling on materials surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That indicates that the V 2 O 5 possesses a better corrosion resistance, and the V 2 O 5 /Ca 0.17 V 2 O 5 has a higher charge transfer rate. , Meanwhile, the corrosion potential ( E corr ) can represent thermodynamic tendency to oxidation or passivation. , The E corr of V 2 O 5 /Ca 0.17 V 2 O 5 is −0.022 V, which is higher than that of V 2 O 5 (−0.047 V). The higher E corr means the V 2 O 5 /Ca 0.17 V 2 O 5 film electrode has a lower thermodynamic tendency to oxidation or passivation, which can be ascribed to the different chemical composition and microstructure. , To understand the electrode reaction kinetics of films, EIS measurements are characterized in Figure b. The Nyquist plots consist of an intercept at a high frequency and a sloping line at a low frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6(b) is the Tafel polarisation curves of the coatings before and after heat treatment, the relevant parameters are determined using the Tafel extrapolation method [37], as shown in Table 3. In general, high corrosion potential ( E corr ) and low corrosion current density ( I corr ) indicate that the material has higher chemical stability and lower corrosion tendency [38,39]. It can be seen that the E corr of all coatings after heat treatment slightly increases, and the I corr decreases.…”
Section: Resultsmentioning
confidence: 99%